2013
DOI: 10.1007/s00330-013-3069-6
|View full text |Cite
|
Sign up to set email alerts
|

Sonoelastography for qualitative and quantitative evaluation of superficial soft tissue lesions: a feasibility study

Abstract: • Sonoelastography helps clarify ambiguous soft-tissue lesions identified using conventional ultrasound techniques. • Addition of this tool increases the diagnostic accuracy of ultrasound. • Sonoelastography provides both qualitative and quantitative analysis. • Sonoelastography may help clinicians improve patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 15 publications
5
43
0
1
Order By: Relevance
“…There was a tendency for malignant masses to be towards the blue spectrum (lower velocities), which is similar to the findings of Magarelli et al and Park et al [16, 17]. The proportion of lesions found to be malignant did not differ substantively between those lesions that where predominantly blue, cyan, or yellow, but those with predominantly red lesions were less likely to be malignant.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There was a tendency for malignant masses to be towards the blue spectrum (lower velocities), which is similar to the findings of Magarelli et al and Park et al [16, 17]. The proportion of lesions found to be malignant did not differ substantively between those lesions that where predominantly blue, cyan, or yellow, but those with predominantly red lesions were less likely to be malignant.…”
Section: Discussionsupporting
confidence: 87%
“…There is only limited published data on the role of sonoelastography in the evaluation of soft tissue masses [16, 17]. The aim of this study was to determine whether quantitative and qualitative shear wave elastography when assessed along with B-mode US imaging could have a role in the evaluation of musculoskeletal soft tissue masses.…”
Section: Introductionmentioning
confidence: 99%
“…13 Magarelli et al 9 reported that SE can be a useful method for evaluation of superficial soft-tissue lesions and that malignant lesions exhibit increased stiffness on SE. Likewise, our study revealed a different SE pattern between malignant tumour and benign tumour, including epidermoid tumour; malignant tumours showed a harder nature than did benign tumours (p , 0.05), but there was no significant difference in the SE pattern between epidermoid tumour and other benign tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Strain elastography (SE) has been introduced for the diagnosis of soft-tissue tumours and is used to evaluate tissue stiffness. 9,10 Hard lesions are more resistant to extrinsic compression and show smaller strain, whereas soft lesions show larger strain. 10 Patel et al 11 reported that most epidermoid tumours show a predominant blue colour, which represents their hard nature.…”
mentioning
confidence: 99%
“…Malignant lesions have been shown to be stiffer on strain elastography compared with benign lesions on a semi-quantitative scale, similar to lesions outside of the musculoskeletal system[50]. However, a recently published study by the group in Leeds assessing the role of shear wave elastography in musculoskeletal tumours has been unable to replicate these early findings, with the authors concluding that there is currently no additional role for shear wave elastography in soft tissue tumours compared with B mode imaging[51].…”
Section: Musculoskeletal Applications Of Elastographymentioning
confidence: 99%